A total evidence analysis of the phylogeny of hatchet-faced treefrogs (Anura: Hylidae: Sphaenorhynchus) - de Araujo Vieira, Katyuscia (2019)
The Neotropical hylid genus Sphaenorhynchus includes 15 species of small, greenish treefrogs widespread in the Amazon and Orinoco basins, and in the Atlantic Forest of Brazil. Although some studies have addressed the phylogenetic relationships of the genus with other hylids using a few exemplar species, its internal relationships remain poorly understood. In order to test its monophyly and the relationships among its species, we performed a total evidence phylogenetic analysis of sequences of three mitochondrial and three nuclear genes, and 193 phenotypic characters from all species of Sphaenorhynchus. Our results support the monophyly of Sphaenorhynchus with molecular and phenotypic evidence, with S. pauloalvini as the earliest diverging taxon, followed by S. carneus, as the sister taxon of all remaining species of the genus. We recognize three species groups in Sphaenorhynchus (the S. lacteus, S. planicola and S. platycephalus groups), to facilitate its taxonomic study; only three species (S. carneus, S. pauloalvini and S. prasinus) remain unassigned to any group. Sequence data were not available for only two species (S. bromelicola and S. palustris) for which we scored phenotypic data; wildcard behaviour was detected only in S. bromelicola nested inside the S. platycephalus group. On the basis of the resulting phylogenetic hypothesis, we discuss the evolution of oviposition site and a number of phenotypic characters that could be associated with heterochronic events in the evolutionary history of this group.